On uses, mis-uses and non-uses of intersectionality before the Court of Justice (EU). Issue 2 (June 2018) - Schiek, Dagmar
Intersectionality, frequently used by political scientists, sociologists and anthropologists as a highly abstract concept, originated as the socio-legal critique, by Kimberlé Crenshaw, of US courts' ignorance of discrimination against Black Women specifically. That ignorance emerged in cases such as DeGraffenreid, in which the claimants challenged a collective redundancy scheme resulting in dismissing all Black Women on grounds of indirect discrimination. The court refused to recognise Black Women as a category of relevance and did not find any discrimination because the scheme did not impact disproportionally on White Women or Black Men. As regards EU law, some socio-legal scholars of today doubt that intersectionality has any value as a practically relevant concept. This article discusses the question whether and how intersectionality can and should be used in applying EU non-discrimination law through a critical analysis of three ECJ rulings delivered between 24 November 2016 and 14 March 2017. The Parris case concerning the pension claims of two white homosexual Men can be qualified as the Court's "DeGraffenreid moment" because it refused to recognise discrimination in a case where the intersection of being over 63 and homosexual was the basis of excluding the Men from a survivor's pension. The Court refused to recognise combined discrimination and found that neither age nor sexual orientation in isolation were the reason of that exclusion. The more recent Achbita and Bougnaoui cases seem to constitute instances of surprising ignorance of racializing Muslim Women through penalising them for wearing a headscarf: The Court, following its Avocates Générales, refused to protect Women against dismissal on grounds of that garment on the basis of extensive justifications for religious discrimination, thus ignoring a pervasive exclusion on the intersection of gender and ascribed race. The article criticises all three rulings with a twofold argument. First, it is submitted that anti-discrimination law should and can recognise intersectional discrimination without losing its focus by a reconceptualization around the nodes gender, race and disability. Second, it is argued that EU anti-discrimination law can be interpreted to encompass this concept by using a purposive interpretation.